Building and evaluating a social prescribing program for carer-employees: an intervention study - Allison M. Williams; Brooke Chmiel; Kate Mulligan; Sarah Neil-Sztramko; Winny Fung; Srija Biswas (Frontiers in Health Services, 2026)
Background Within a 12-month time window, and in partnership with the Canadian Institute for Social Prescribing (CISP), an extension of the Canadian Red Cross (CRC), we will develop and test a social prescribing (SP) program intervention in Hamilton, Ontario, Canada for Carer-Employees (CEs) - those who balance unpaid care of an adult dependent with paid employment. Given the emergence of SP programs geared towards unpaid carers more broadly, the development of an SP program specific to CEs will provide coordinated access to social and community supports that are unique to the needs of CEs in balancing their dual role. Methods OBJECTIVE 1: Informed by a recently completed scoping review of SP programs for CEs, the team will work closely with partner organizations, CISP and the CRC, and a Project Advisory Committee (PAC), including CEs with lived experience, to develop an SP program intervention via a co-design approach drawing on design thinking techniques and collective impact initiative backboned by CISP's SP pathway. The SP program will then be used as an intervention to be tested in the province of Ontario, Canada, via OBJECTIVE 2. OBJECTIVE 2: Using a sequential exploratory mixed-methods design, four Plan-Do-Study-Act (PDSA) cycles (a problem-solving model for improving the SP intervention program) will refine the implementation characteristics of the developed SP program and explore its impacts on CE health. The intervention(s) will operate as a quasi-experiment, where a quasi-experimental pre-post design will be conducted within each PDSA cycle, allowing the SP intervention to be tested and refined with respect to potential adoption by CEs. Impacts on CEs’ health will be determined within each PDSA cycle, specifically on CEs’ mental, psychosocial, and physical health. Quantitative and qualitative data will be generated within each cycle to inform refinements to implementation. A wait-list control group will be randomly assigned to ensure that the observed improvements can be attributed to the intervention. Discussion Given the national reach and scope of CISP and the CRC, their commitment to the present initiative provides the project team with the resources necessary to build an effective SP program for CEs in Ontario, while also establishing sustainability through the expansion of this SP program across Canada. The final SP program will be scaled up to the national level.